'There seems to be some misunderstanding': church-state relations and the establishment of Carraroe comprehensive, 1963–67. Issue 1 (2nd January 2023) - Delaney, Catriona
Abstract : This paper charts the development of one of Ireland's first comprehensive schools located in Carraroe in County Galway. Through a systematic, historical analysis of Department of Education and diocesan correspondence, this article provides a unique insight into how official policy was reconciled at ground level. The analysis exposes the ambiguity of previous studies surrounding the role of the church hierarchy in educational reform during the 1960s and seeks to clearly identify key personnel involved in consolidating policy concerning the comprehensive school scheme. Underpinning this narrative, is the deliberate exclusion, by both church and state, of local school authorities from policy decision-making regarding the comprehensive school in Carraroe. In particular, this paper illustrates how a paradigm shift in Department of Education negotiation tactics provided the government with an effective means for introducing new educational policy measures in the future.